Removal of iron from wastewater using a hybrid filter. Issue 1 (July 2020) - Abdulla, Gameel; Kareem, Mohanad Mousa; Hashim, Khalid S.; Muradov, Magomed; Kot, Patryk; Mubarak, Hayfaa A.; Abdellatif, Mawada; Abdulhadi, Bareq
Abstract: Limestone is originally generated from sedimentary rocks that are mainly made from CaCO3, the latter in turn is made from calcites and aragonites. This chemical composition of limestone makes it a suitable material for water/wasters treatment as these elements are identified for their capability to adsorb several pollutants. Although, limestone is environmentally sustainable material and is broadly applied in water filtration, it is has a moderate affinity for heavy metals. Thus, due to this serious drawback, limestone becomes less attracting for researchers. Therefore, this study is aiming at producing an environmentally sustainable filtration system by mixing limestone and activated carbon, and applies it to remove heavy metal (iron) from synthetic wastewaters. The ability of the new filtration media, which was made of 50% activated carbon and 50% limestone (1:1 ratio), to remove iron from 10 mg/L synthetic iron solution. The latter was created using ferrous sulphate heptahydrate and deionised water. The removal of iron was optimised for the influence of the absorbent dosage (AD) (500-1000 g), detention time (DT) (10-120 minutes) and pH of solution (4-10). The outcomes of the experiments evidenced the capacity of the new filter to efficiently remediate wastewater from iron. Where, 1000 g of this filter needed only 95 minutes, at pH of 6.0, to completely remove iron ions from the synthetic solution.